The Use of Mediated Instruction of Text (MIT) Strategy in Teaching Reading Comprehension - Nora Fitria; Sariakin Sariakin; Ratna Fitra Saiful (Universitas Serambi Mekkah, 2021)
The study was aimed to find out if there is a significant difference between the eighth grade students of SMP Negeri 13 Banda Aceh who are taught reading comprehension by MIT strategy and those who are taught without using MIT strategy. This study belonged to experimental study. The population of this study was all of the eighth grade students of SMP Negeri 13 Banda Aceh in the academic year of 2017/2018. The total population was 151 students who were composed of five classes; class VIII1, class VIII2, class VIII3, class VIII4, and class VIII5. The sample of this study was taken randomly with the total of 70 students, 35 students in experimental group and 35 students in control group. Choosing class as experimental and control group was also done randomly. The data were gotten through test; pre-test and post-test. The data were analyzed by using SPSS 18.0. The result of the study showed that there was a significant difference between the eighth grade students of SMP Negeri 13 Banda Aceh who are taught reading comprehension by using MIT strategy and those who are taught without using MIT strategy. It can be proven from the result of this study, where the result of t-test of post-test for both group was 3.07. While the result of t-table with the level of significance 0.05 was 0.67. Thus, t-test (3.07) was greater than the t-table (0.67). Based on the result of the study, English teachers of SMP Negeri 13 Banda Aceh, especially those who teach reading comprehension, should implement MIT strategy in teaching and learning process because the implementation of the strategy can increase the students’ reading comprehension mastery.